Early Child Welfare Policy and Services in Colonial Malaya - Fuziah Shaffie (International Review of Management and Marketing, 2016)
Social welfare policy and services has not received attention from scholars it deserves. Scholars intent on learning about early child welfare policy in Malaysia would be confronting challenging difficulties to obtain appropriate documented sources, since reference are readily available. This paper discusses the essential welfare services provided by the Department of Social Welfare (DSW) during the period of 1946-1957 under the British Colonial Government. As the major agency authorised to provide child care and protection in Malaya, the DSW had to deal with, among others, post-war social issues that needed immediate attention. It focused on issues during the post-war period that triggered the government’s desire to provide services to ensure the well-being of children. The paper also explains the DSW programmes designed to meet the children’s needs. It highlights the involvement of voluntary associations and other governmental departments towards the well-being of children. Also, this paper highlights other services, namely, blind welfare, delinquent children, and vagrancy. The use of archival sources in a sense had contributed to support and validate the researcher’s secondary data.